2013
DOI: 10.1177/1527154413481811
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Amidst Change

Abstract: This article aims to clarify the concept of change fatigue and deems further exploration of the concept within the discipline of nursing is relevant and necessary. The concept of change fatigue has evolved from the discipline of management as a means to explore organization change and its associated triumphs and failures. Change fatigue has typically been described as one and the same as change resistance, with very little literature acknowledging that they are in fact distinct concepts. Concept clarification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 20 publications
1
80
0
Order By: Relevance
“…Demonstrated within this study is evidence consistent with other studies that change fatigue is a phenomena that develops over time (Bernerth et al, 2011;McMillan & Perron, 2013). Although not analyzed within the context of this study, further analysis in to the subcategories of Group data may support prior research on nursing teams.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Demonstrated within this study is evidence consistent with other studies that change fatigue is a phenomena that develops over time (Bernerth et al, 2011;McMillan & Perron, 2013). Although not analyzed within the context of this study, further analysis in to the subcategories of Group data may support prior research on nursing teams.…”
Section: Discussionsupporting
confidence: 85%
“…The effects of continuous change and subsequent coping are often overlooked by higher levels of management in health care organisations, especially from a nursing perspective (Brown, 2016;McMillan & Perron, 2013). It has also been suggested that in any large-scale project, change fatigue should be considered a normal variant (Winter, 2013), especially in new organisations where there may be a general assumption that change is excessive (Rafferty & Griffin, 2006in Bernerth et al, 2011 .…”
Section: Coping With Large-scale Organisational Changementioning
confidence: 99%
See 2 more Smart Citations
“…Change fatigue is different from resistance to change (McMillan & Perron, 2013). Had the team reached their capacity-were they fatigued with the amount of change?…”
mentioning
confidence: 99%